Ubicación óptima de unidades de medición fasorial para la observabilidad de sistemas de potencia usando un algoritmo evolutivo. - Tacle Mora, Leyton Fernando (2022)
This research focuses on solving the problem of Optimal Location of Fasorial Measurement Units (PMU). Whereas they are devices to monitor and manage the electrical system in an appropriate manner and in real time; This equipment provides measurements of electrical variables such as voltages, currents and phase angles nodes where it be installed. This document proposes a methodology to solve this problem so that the distribution system is completely observable under nominal operating conditions and considering the effect of Zero Injection Nodes (ZINs). The genetic algorithms method is used with the help of MatLab software to find the minimum number of devices so that the system is 100% observable, the IEEE standards of 14 and 30 buses are used for this. At the end it was possible to produce comparable results to other available techniques.